On the early history of Val Resia and some of its toponyms or: How the Resians lost their name - Steenwijk, Han (Slovenski jezik / Slovene Linguistic Studies, 2023)
On the basis of the earliest toponyms and administrative documents pertaining to Val Resia a hypothesis on the Alpine Slavic settlement, the original name of these settlers and the early Medieval development of the valley is proposed. The identical name for the village of San Giorgio and for the valley as a whole during this period turns out to be an important fact in favour of this hypothesis.